THE STUDENTSâ ABILITY IN READING AT URBAN AREA AND AT REMOTE AREA - Masruddin, Masruddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2016)
This research is aimed at 1) finding out the ability of students in reading descriptive text of theÂ Â  secondÂ  year students at SMPN 1 Limbong as remote area school and SMPN 1 Baebunta as urban area school. 2) finding out whether there is a significant difference between the ability of students at urban and at remote area school in their competencies in reading descriptive text. In this research, the writer applied descriptive method. The sample of the research were 50Â  students at SMPN Limbong and 50 at SMPN Baebunta. The instrument of this research was reading test.Â  It consisted of 3 reading descriptive text with 15 questions.Â  The results of the research shows that the mean score of students in SMPN 1 Limbong was very- different with their mean score in SMPN 1 Baebunta.Â  The mean score of SMPN 1 Baebunta was 5.06 while the mean score ofÂ  SMPN 1 LimbongÂ  wasÂ  3.11.Â  Furthermore, it can be seen from the t test result which shows that the result of t-test was greater than t-table. The value of t table was 2.02. while the t test was 7.46.Â  it means that t-test was greater than t-table or 7.46> 2.02.Â  This is indicated that to â¥ ttÂ  so, null hypothesis (ho) is rejected and alternative hypothesis (hi)Â  is accepted, therefore in can be said thatÂ  there is a significance different between the studentsâ achievement at SMPN 1 Limbong and SMPN 1 Baebunta. This research proves that the urban area school is better than the remote area school in reading descriptive text achievement.